Biobanking of human biological material and the principle of noncommercialisation of the human body and its parts. (13th December 2022) - Pawlikowska, Joanna; Pawlikowski, Jakub; Krekora‐Zając, Dorota
Abstract: The prohibition of commercialisation of the human body and its parts is not applied consistently and suffers from many exceptions in the human biological material (HBM) market. Examples include the possibility of patenting certain HBM‐derived products and their commercial marketing or payments for blood donations. Thus, the current practice of marketing HBM‐derived products makes the altruistic donor most vulnerable to exploitation while being deprived of benefits. There seem to be two ways to improve this state of affairs. The first is to apply consistently the prohibition of commercialisation of the body and its parts to commercially marketed tissue and cell products as well. This would require limiting the possibility of financial gain associated with the processing, distribution and sale of HBM‐based products. Such a solution, however, does not seem to gain wide acceptance or have a chance of implementation in the near future. Therefore, introducing more transparent rules and greater donor empowerment seems more reasonable by exempting HBM from the ban on commercialisation under certain conditions and with clear limitations.